Pleistocene Carnivora (Mammalia) from Tighennif (Ternifine), Algeria - (:unkn) unknown (My University, 2016)
The site of Tighennif (= Ternifine) in Northern Algeria, well-known for its Homo mauritanicus (= Homo rhodesiensis?) remains, and probably dating to the late Calabrian, yielded a large assemblage of terrestrial carnivores. Some are identical or probably identical with extant species: Crocuta crocuta and Hyaena hyaena (Hyaenidae), Felis silvestris (Felidae), Mellivora capensis and Poecilictis cf. libyca (Mustelidae), and Vulpes cf. rueppelli (Canidae). In addition, among felids there is an unidentified leopard-like form; a smaller, more common species assigned to Lynx sp. (a genus quite rare in Africa) but which is certainly different from modern forms, an Homotherium that seems to be the last occurrence of the machairodonts in Africa, and a Panthera aff. leo, which is unfortunately too poorly known to be named. Rare bears do not display all derived features of later North African U. bibersoni. Among canids, the Nyctereutes-like jackal Lupulella mohibi is an endemic North African form known until the late middle Pleistocene, and the hunting dog Lycaon magnus is also clearly distinct from the modern species. A single new species is described, Enhydrictis hoffstetteri, a large, otter-like member of the Mustelidae, of a genus that was previously unknown from Africa, and certainly testifies to North-South dispersal across the Mediterranean at some time during the early Pleistocene.
Keywords: African Research